(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The mandatory vertical distortions of the foundations were investigated by V.I.Ilichev, D.D. Barkans based on experiments. Based on the experiments, written by D.D. Barkan and B.M.Mardonov, "The theorem of the theorems is based on the current history of the world, for more information, please first appear in the article "The Bible’s Viewpoint: How Can I Make Bible Teaching Enjoyable?"